Synthesis and study of gas sensitive ZnFe2O4-modified ZnO nanowires. Issue 1 (1st March 2022) - Aubekerov, K; Punegova, K N; Sergeenko, R; Kuznetsov, A; Kondratev, V M; Kadinskaya, S A; Nalimova, S S; Moshnikov, V A
Abstract: Currently, new nanostructured materials based on composite metal oxides is of great interest for the development of gas sensors with improved functional characteristics. In this work, zinc oxide nanowires were synthesized by hydrothermal method. Hierarchical ZnO/ZnFe2 O4 nanostructures were obtained by immersion of zinc oxide layers in ferrous sulphate aqueous solution. The mechanism of zinc ferrite formation during the interaction of zinc oxide with iron sulphate is considered. The crystal structure of ZnO and ZnO/ZnFe2 O4 were studied by Raman spectroscopy. The sensitivity of ZnO and ZnO/ZnFe2 O4 nanostructures to isopropyl alcohol vapors was analyzed. It was shown that there is an optimal concentration of ferrous sulphate used to modify zinc oxide nanowires and synthesize ZnO/ZnFe2 O4 composite nanostructures.